Effects of red onion peel extraction, Allium cepa on some productive performance and lipid profile status of broiler exposed to heat stress - Zaid Mowfaq Abdalkarem; Mayada F. Mohamed (Caspian Journal of Environmental Sciences)
This study was carried out to see how adding Allium cepa peel extract can affect growth performance and lipid profile of the broiler chicken after heat stress. At first, the peels of red onion have been extracted using hot water. A total of 300 one-day-old chicks were examined. This experiment lasted for 28 days and employed a completely randomized design. The birds were grouped into 5 treatments (C-, C+, T1, T2, and T3). Group C- fed with basal diet without any addition; C+ fed a basal diet with 0.5% synthetic antioxidant BHT; T1 fed basal diet + 3% red onion peels extract; T2 with basal diet + 6% red onion peels extract and T3 with basal diet + 9% red onion peels extract. In 30th day, all birds were exposed to heat stress by raising temperature to 30 ºC. Data were collected about feed intake and weight gain weekly. The results of the body weight performance of chicks were studied. The statistical analysis revealed that there was a significant (p < 0.05) elevation in productive performance of onion-supplemented groups, compared to the control positive and negative in dose-dependent manner. Furthermore, the results of the lipid profile revealed that all groups supplemented with red onion peel extracts (T3, T2, and T1 respectively) experienced significantly (p < 0.05) reduced triglycerides, total cholesterol, low-density lipoprotein, and very low-density lipoprotein compared to control groups. However, they exhibited an insignificant effect on high-density lipoprotein and very low-density lipoprotein concentrations in comparison with the control group. In conclusion, dietary supplementation of red onion peel extract enhanced body weight gain, tissue antioxidants, lowered serum total cholesterol, triglycerides, and an immunomodulatory effect in a dose-dependent manner.